Β-Thalassemia Intermedia Caused by Compound Heterozygosity for Hb Lepore-Hollandia and β-Thalassemia is Rare in the Indian Population. (3rd September 2015) - Sreedharanunni, Sreejesh; Chhabra, Sanjeev; Hira, Jasbir Kaur; Bansal, Deepak; Sharma, Prashant; Das, Reena
Abstract: Compound heterozygosity for one of the Hb Lepore mutations and β-thalassemia (β-thal) is a rare cause of non transfusion-dependent thalassemia. We report a 4-year-old boy who presented clinically as homozygous/compound heterozygous β-thal intermedia (β-TI), an impression that was corroborated by the initial hemoglobin (Hb) high performance liquid chromatography (HPLC). However, the correct diagnosis of a rare compound heterozygous Hb Lepore-Hollandia/β-thal was revealed after parental studies and molecular analyses including β-globin gene sequencing. Our patient highlights the importance of a logical stepwise multi modality approach and the vital importance of parental screening and molecular studies in accurate characterization of complex hemoglobinopathies. Correct diagnosis is especially crucial if pre natal detection is anticipated for future pregnancies. Molecular analyses alone may not compensate for the unavailability of parental testing. This is because the molecular results may be misinterpreted, especially if limited tests are conducted. The infrequent prior reports of this combination from distant parts of the Indian subcontinent suggests that the origin of Hb Lepore-Hollandia from sporadic mutations occurs in isolated families.